3x+2(x-6)=12

Simple and best practice solution for 3x+2(x-6)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+2(x-6)=12 equation:


Simplifying
3x + 2(x + -6) = 12

Reorder the terms:
3x + 2(-6 + x) = 12
3x + (-6 * 2 + x * 2) = 12
3x + (-12 + 2x) = 12

Reorder the terms:
-12 + 3x + 2x = 12

Combine like terms: 3x + 2x = 5x
-12 + 5x = 12

Solving
-12 + 5x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 5x = 12 + 12

Combine like terms: -12 + 12 = 0
0 + 5x = 12 + 12
5x = 12 + 12

Combine like terms: 12 + 12 = 24
5x = 24

Divide each side by '5'.
x = 4.8

Simplifying
x = 4.8

See similar equations:

| 7=-13+.4b | | 180-2x-6=124 | | -(((sin(x)+1)*sin(x-cos(x))-1)*sin(x+cos(x-cos(x)))-1)*cos(x-cos(x+cos(x-cos(x))))=0 | | -7=-13+.4b | | 3n+8+n=28 | | 6+13n=25780 | | 6y+2=4y+8 | | 7(x-21)=35 | | -h+9=-29 | | -(-2y+3w-8x)= | | 10(5-4y)=20 | | (2x+15)=x+15 | | f(x)=-4x^2-8x-3 | | y=(4+7)(4-4)(2(4)-3) | | y-4=15-2y | | -3(8)(8-10)-6(5-3(8))= | | f(x)=4x^2-8x-3 | | D/7=3.8 | | y=(-7+7)(-7-4)(2(-7)-3) | | 38=.5*3(7+b) | | 120+(-7)n=0 | | -6/5-6y=9 | | (2t-5)(2t+5)=0 | | 20=5(h-7) | | 61+2x=90 | | 2x+61=90 | | -6(x-7)=10 | | 4x^2-y^2-6y-9=0 | | -29+4x=-39+9x | | 2/3x-2=22 | | (3x-28)-(66-x)=180 | | 3/7p=6 |

Equations solver categories